Hematotoxic, oxidative and genotoxic damage in rainbow trout (Oncorhynchus mykiss) after exposure to 3-benzoylpyridine. (2nd September 2022) - Parlak, Veysel; Ozgeris, Bünyamin; Ucar, Arzu; Cilingir Yeltekin, Aslı; Ozgeris, Fatma Betul; Cağlar, Ozge; Alak, Gonca; Turkez, Hasan; Atamanalp, Muhammed
Abstract: Pyridine is a basic heterocyclic organic compound. The pyridine ring is present in many important compounds, including agricultural chemicals, medicines and vitamins. Due to their widespread industrial use, bioaccumulation and non-target toxic effects are being considered as a great risk to human and environmental health. In this study, we aimed to evaluate the hematological, oxidative and genotoxic damage potentials by different concentrations (1, 1.5, and 2 g/L) of the ketone 3-Benzoylpyridine (3BP) on rainbow trout ( Oncorhynchus mykiss ). Alterations in the biomarker levels of oxidative DNA damage (8-hydroxy-2′-deoxyguanosine (8-OHdG)), apoptosis (Caspase-3), malondialdehyde (MDA) as well as antioxidant enzyme activities including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), myeloperoxidase (MPO), paraoxonase (PON), and arylesterase (AR) were assessed in brain, liver, gill and blood tissues. Acetylcholinesterase (AChE) activity was also determined in brain tissue. In addition, we analyzed micronucleus (MN) rates and hematological indices of total erythrocyte count (RBC), total leukocyte count (WBC), hemoglobin (Hb), hematocrit (Hct), total platelet count (PLT), mean cell hemoglobin concentration (MCHC), mean cell hemoglobin (MCH), and mean cell volume (MCV) in blood. LC50 -96h value of 3BP was calculated as 5.2 g/L from the data obtained. A significant decrease in brain AChE activity was determined in clear time and dose dependent manners. While SOD, CAT, GPx, PON, and AR levels were decreased, MDA, MPO, 8-OHdG and Caspase-3 levels were increased in all tissues ( p  < 0.05). Again, the 3BP led to increases of MN formation at all applied concentrations in the rates of between 45.4 and 72.7%. Significant differences ( p  < 0.05) were found out in between all studied hematology parameters between 3BP-exposed and the control fish. In conclusion, ours study firstly indicated that the treatment doses of 3BP induced distinct hematological and oxidative alterations as well as genotoxic damage in rainbow trout.